Epidemiological Patterns of Breast Cancer Prevalence in Libya: A Retrospective Descriptive Analysis (2015–2024) - Almabrouk Alhireereeq; Elkhouly A. R. (African Journal of Advanced Pure and Applied Sciences, 2026)
Background: Breast cancer is a significant health concern in Libya, as it is the most common malignancy among Libyan women. The incidence and characteristics of breast cancer in Libya reflect broader regional trends, with unique local factors influencing its epidemiology. Aims: The aim of this research was to present a contemporary analysis regarding the prevalence of breast cancer cases in Libya. Methods: A retrospective descriptive analysis was conducted using data collected from 2,942 confirmed breast cancer cases recorded between 2015 and 2024. Cases were analyzed based on annual incidence, regional distribution across twenty areas, sex, five age groups, and diagnostic categories (right breast lump, left breast mass, and bilateral breast cancer). Descriptive statistics were used to summarize frequencies and percentages. Results: The highest annual incidence was observed in 2024, accounting for 426 cases (14.6%), while the lowest incidence occurred in 2017 (206 cases; 7%). Regionally, Alzawia reported the highest number of cases (577; 19.7%), whereas Misurata recorded the lowest (2 cases; 0.07%). Females constituted the majority of cases (97.5%), compared to males (2.5%). The most affected age group was 47–63 years (40.5%), followed closely by individuals aged 30–46 years (39.6%). Bilateral breast cancer was the most common diagnostic category (39.2%). Age- and diagnosis-specific analyses revealed that unilateral breast lesions were most prevalent in the 30–46-year age group, while bilateral cases peaked among those aged 47–63 years.